SEBARAN UKURAN BUTIRAN SEDIMEN GISIK SEKITAR GROIN PANTAI KALASEY - Manengkey, Hermanto WK (Sam Ratulangi University, 2011)
ABSTRACTThis study was conducted to examine the effectiveness of groins built along one of the littoral area in the coastal region of Manado. Logically, in this region the marine processes is strong enough to bring out the sediment, which is why in this area was built groin structures as shore protection. Groin is a structure designed to keep beach sand from being transported away by longshore current or to reduce the transportion of sand. This study was conducted by observing the size distribution of beach sediments around the groin in Kalasey beach. The groins on the Kalasey beach analized for their beach sediment samples were 8 units with 22 beach sediment sample collection spaces. Sediment samples were processed in the laboratory through washing and drying. The sediment was then separated with a sieve. Sediment left on each sieve is weighed and the weights were plotted. This study shows that the presence of groins in Kalasey beach was apparently quite effective to withhold the flow of sediment transport because of longshore current in this shore area.Keywords:.sediment size distribution, groin, Kalasey beach, Manado.ABSTRAKPenelitian ini dilaksanakan untuk melihat efektivitas groin yang dibangun di sepanjang litoral salah satu area dalam kawasan pantai Manado. Secara logis, pada kawasan ini proses laut cukup kuat dalam membawa sedimen keluar, itulah sebabnya sehingga pada kawasan ini dibangun struktur pelindung pantai berupa groin. Groin merupakan salah satu bangunan pelindung pantai yang direncanakan untuk menahan angkutan pasir oleh arus susur pantai (longshore current) atau mengurangi angkutan pasir. Penelitian ini dilakukan dengan mengamati keberadaan sebaran ukuran sedimen gisik yang terhampar di sekitar groin tersebut. Rangkaian groin di pantai Kalasey yang dianalisis sampel sedimen gisiknya adalah sebanyak 8 buah groin dengan 22 ruang pengambilan sampel sedimen. Sampel sedimen ditangani di laboratorium dengan melakukan pencucian dan pengeringan. Setelah kering, sedimen dipisahkan dengan ayakan. Sedimen yang tertinggal di masing-masing ayakan ditimbang dan hasilnya digambarkan dalam grafik peubah distribusi granulometri. Penelitian ini menunjukkan keberadaan groin di Kalasey ini tampaknya cukup efektif menahan laju arus susur pantai dalam mengangkut sedimen keluar dari kawasan pantai ini.Kata kunci: distribusi ukuran sedimen, groin, pantai Kalasey, Manado.